2012
DOI: 10.1177/0255761411433728
|View full text |Cite
|
Sign up to set email alerts
|

Two studies of pitch in string instrument vibrato: Perception and pitch matching responses of university and high school string players

Abstract: We investigated pitch perception of string vibrato tones among string players in two separate studies. In both studies we used tones of acoustic instruments (violin and cello) as stimuli. In the first, we asked 192 high school and university string players to listen to a series of tonal pairs: one tone of each pair was performed with vibrato and the other without. Violin tones with vibrato were judged as lower in pitch than non-vibrato stimuli with the same mean frequency, more so among high school string play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 20 publications
0
9
1
11
Order By: Relevance
“…Considering the findings of the present study and those of Worthy, we find it ironic that one of the synonyms for timbre is tone color. We found no significant differences in pitch or timbre production based on the experience level of the participants (high school vs. college), a finding that is inconsistent with previous research indicating superior tuning accuracy among college instrumentalists over high school instrumentalists (Byo & Schlegel, 2016;Geringer et al, 2014;Schlegel & Springer, 2018). It is unclear why participants in this study demonstrated no significant differences on the basis of experience level.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Considering the findings of the present study and those of Worthy, we find it ironic that one of the synonyms for timbre is tone color. We found no significant differences in pitch or timbre production based on the experience level of the participants (high school vs. college), a finding that is inconsistent with previous research indicating superior tuning accuracy among college instrumentalists over high school instrumentalists (Byo & Schlegel, 2016;Geringer et al, 2014;Schlegel & Springer, 2018). It is unclear why participants in this study demonstrated no significant differences on the basis of experience level.…”
Section: Discussioncontrasting
confidence: 99%
“…(Praat is open-source software that can be used to measure various aspects of pitch and other spectral elements of sound; technical details of the software and spectral analysis details were summarized by Weenink, 2020 andStyler, 2017. ) Due to the pitch variation and noise that occurs at the attack and release, we analyzed only the middle 2 seconds of each tone to determine mean frequency, similar to protocols used in previous studies (Atkins, 2018;Byo & Schlegel, 2016;Geringer et al, 2014;Schlegel & Springer, 2018). Once we determined the mean frequency, we compared that value to the equal-tempered standard in each octave to determine the cent deviation, which we expressed in absolute value.…”
Section: Dependent Measuresmentioning
confidence: 99%
“…We limited our skill level by barring students who might use vibrato. Vibrato is not a beginner technique and was potentially problematic for the study as reliably identifying and interpreting heard vibrato pitch is challenging (Brown and Vaughn, 1996; Geringer et al, 2014; Yang et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Sources of stimulus variability in music include global factors like instrument range and timbre, which can affect pitch judgments (Byo, Schlegel, & Clark, 2011;Geringer, MacLeod, Madsen, & Napoles, 2015;Wapnick & Freeman, 1980). Timbre varies within instruments, as well, depending on the intentions and skill of the performer and performance factors such as the presence of vibrato (Geringer, MacLeod, & Ellis, 2014;Geringer, MacLeod, & Sasanfar, 2015). Even the emotional state of the performer can affect tempo, dynamics, rhythm, and attack slope (Van Zijl, Toiviainen, Lartillot, & Luck, 2014).…”
Section: Musical Normalizationmentioning
confidence: 99%